Does nitrogen fertilization rate, timing and splitting affect sunflower yield and grain quality? - Tovar Hernandez, Sergio (2023)
Nitrogen (N) deficiency could have a negative effect on sunflower (Helianthus annuus L.) yield and grain quality. Therefore, it is necessary to adjust the optimum rate, timing, and frequency of N fertilization to improve sunflower crop nutrition. Our objective was to evaluate the effect of N fertilization rate, timing, and splitting on grain yield, and grain and oil quality. Twelve field experiments were carried out between 2016 and 2020. Treatments consisted of at least three N rates ranging from 0 to 200 kg N ha−1 applied at V2. Moreover, the 80 kg N ha−1 rate was applied at V14 (80NV14) or split between V2 and V14 (80Nsplit). Treatments were evaluated in two sunflower genotypes, high oleic (HO) and conventional (CONV). A significant grain yield response to N fertilization was observed in six out of twelve experiments, generally at rates greater than 80 kg ha−1. The mean response to fertilization was 369 kg ha−1. Fertilization increased grain protein concentration (PG) (+1.5%) at experiments E1–E3 and E9–E12 and decreased oil concentration (OG) (−2%) at experiments E1, E4, E9, E11, and E12. The maximum N rate, increased oleic and stearic acid concentration (+3%–4%), depending on the genotype (AO and CONV). Neither fertilizer timing nor splitting affected grain yield or OG. Late N fertilization (V14) increased oleic acid (+2.4%), whereas it decreased linoleic acid (+2.2%). Based on our results, N fertilization can increase yield without negatively affecting commercial grain quality (OG and fatty acids concentration), regardless of fertilization timing and frequency.